Genomic bases of morphometric variations in small ruminants of Morocco - Ouhrouch A.; Boitard S.; Boyer F.; Da Silva A.; Servin B.; Pompanon F.; Haddioui A.; Benjelloun B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Small ruminants are one of the main sources of meat and milk around the world. The improvement and conservation of these species constitute major challenges for their sustainable contribution to the needs of human populations. Some morphological variations of individuals reflect the diversity of their adaptive potential and their zootechnical performances. The aim of this work is to analyze whole genome data of 160 unrelated local sheep, at a depth of 12X, sampled to represent the ecological and geographical diversity of Morocco. It aims at studying the genomic bases of their phenotypic variations by associating the genomic variations noted with the best possible resolution of the genomes (sequences of the complete genomes) with a certain number of morphometric indicators which affect the adaptive potential (ie. ears length) or the productive potential (ie. shoulder height, barrel tour). This association, carried out via genome wide association approaches (GWAS) will make it possible to highlight the possible genomic mutations responsible for these variations, among which we can identify those involved in adaptation to different climatic environments and those linked to the best zootechnical performances. These mutations should make it possible to incorporate these variations, after their validation, into selection schemes to improve the productivity of these species and their adaptability to certain climatic conditions.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)